The Educational and Professional Careers of Women in Poland - Dorota Raczkiewicz; Marta Dolecka (Barometr Regionalny, 2013)
Both women and men in their lives have at least two careers: educational and professional. These careers can differ according to gender. The aim of this paper is to analyze educational and professional career differences between men and women using some macro indicators to correlate these two career indicators, as well as to investigate the diversity of the indicators among regions in Poland and other European Union countries, and to establish the position of Poland within the EU with respect to these indicators.